Implementation of the Andragogy Approach in the Service Program for Islamic Boarding School Alumni - Khasani, M. Taufan; Muhajirin, Muhajirin; Munir, Munir (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the implementation of the andragogy approach in the alumni service program of Islamic boarding schools as an effort to prepare quality human resources. The focus of the study is directed at the construction of program inputs, processes, and outputs with an emphasis on the principles of adult learning. This study is a qualitative, multisite study designed to gain an in-depth understanding of the application of the andragogical approach in the context of Islamic boarding school education in various locations. The research was conducted at several Islamic boarding schools in the South Sumatra region, including Ogan Ilir Regency, Ogan Komering Ilir Regency, and Palembang City, which have a strong tradition of organizing alumni service programs. Data were collected through in-depth interviews, observations, and documentation. Data sources consisted of alumni who participated in the community service program, pesantren leaders, supervising ustadz, and the surrounding community who interacted directly with program participants. Data analysis was conducted using Miles and Huberman's interactive model, through the stages of data reduction, data presentation, and conclusion drawing, which were verified through triangulation. The results of the study show that the input aspect is reflected in the readiness, motivation, and learning experiences of alumni, which are the main assets in adult learning. The process aspect shows the application of andragogical principles such as independent learning, problem-solving orientation, and active involvement in teaching and organizational tasks. Meanwhile, the output aspect shows the development of alumni competencies as prospective educators and community leaders, marked by increased pedagogical skills, leadership capacity, and social responsibility. This study concludes that alumni service programs designed with an andragogical perspective can improve the quality of Islamic boarding school graduates and contribute significantly to strengthening Islamic education. These findings emphasize the importance of strengthening Islamic boarding school programs through contextual andragogical strategies so that the potential of alumni can be optimized in facing contemporary educational and social challenges.